Knowledge of Neonatal Danger Signs and Its Associated Factors among Mothers Attending Child Vaccination Centers at Sheko District in Southwest Ethiopia - Tewodros Yosef; Tadesse Nigussie; Adane Asefa (International Journal of Pediatrics)
Background. Even though a great improvement in the last twenty years, the problem of newborn deaths is still remaining. In 2017 alone, an estimated 2.5 million neonatal deaths occurred worldwide, around 39 percent of all deaths in sub-Saharan Africa. Early detection of neonatal illness is an important step towards improving newborn survival. If mothers know the appropriate manifestations of the causes of death in newborns (neonatal danger signs), it is possible to avert related mortality, because of the health-seeking behavior of mothers highly relies on their knowledge of neonatal danger signs. Objective. To assess knowledge of neonatal danger signs and its associated factors among mothers attending child vaccination centers at Sheko District in Southwest Ethiopia. Methods. A facility-based cross-sectional study was conducted among 351 mothers who attended health centers for child vaccination in Sheko District from March 17 to April 30, 2018. A consecutive sampling method was used to select study participants. Data were collected by using structured questionnaires through face-to-face interviews. Data were entered using EPI-DATA version 3.1 and analysed using SPSS version 21. Results. Of the 351 mothers interviewed, 39% (137) had good knowledge of neonatal danger signs. The study also found that mothers aged 29-40 years (AOR=2.37, 95% CI [1.35-4.17], P=0.003), educational status of primary and above (AOR=2.68, 95% CI [1.48-4.88], P=0.001), attending ≥ 4 antenatal care visits during pregnancy (AOR=3.57, 95% CI [2.10-6.06], P<0.001), and history of postnatal attendance after birth (AOR=2.33, 95% CI [1.16-4.65], P=0.017) were significantly associated with good knowledge of neonatal danger signs. Conclusion. The proportion of mothers with good knowledge of neonatal danger signs was remarkably low. Since the problem is a public health importance in developing countries, particularly in Ethiopia, which determines future generations. Great efforts are needed to create awareness for mothers on the importance of the early identifying neonatal danger signs plus to avert the high magnitude of neonatal mortality.